The Impact of Transmission and Distribution Price Reform on Economic Growth in Liberalized Electricity Markets: An Inter-Provincial Panel Data Analysis - Li, Hong; Wang, Xiaogang; Xie, Yuantao; Chen, Ting; Han, Haoming; Yang, Yichen (Frontiers in Environmental Science, 2022)
How electricity prices affect regional economic growth has been a concern of the government and academia in recent years.This article attempts to take the power transmission and distribution price reform in the power system reform as a starting point, using provincial panel data from 2010 to 2019, and adopting a progressive difference in differences method (DID) to conduct a systematic and rigorous empirical study on the policy effects of the transmission and distribution price reform. The research results show that: First, the reform of transmission and distribution price has significantly promoted the growth of regional GDP and regional GDP per capita. Second, with the help of the introduction of market pricing mechanisms in cross-province and cross-regional power transactions, it is found that the level of power and electricity prices changes in the same direction as the level of economic development.Third, the electricity price reform promotes regional economic growth by promoting the continuous optimization of the regional industrial structure.This not only provides theoretical confidence and important policy enlightenment for our country to continue to deepen the market-oriented reform of the electricity system, but also provides theoretical and empirical evidence support to a certain extent for the implementation of the high electricity price model under the new situation.